The Impact of Greenwashing in Sustainable Finance on Stock Performance - Bojcovová, Andrea; Teplý, Petr, 1977-; Škrabka, Jan; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2025)
This bachelor thesis examines the phenomenon of greenwashing in the context of sustainable finance and its effect on stock performance. The thesis is divided into three parts. The first part provides a theoretical overview, outlining the origins of sustainable finance, defining greenwashing, and presenting key regulations addressing it across various regions. The second part focuses on empirical analysis through two case studies: the impact of greenwashing allegations against HSBC in the banking sector, and several environmental controversies involving Shell in the oil and gas sector. Both analyses use market data and quantitative methods to test three hypotheses concerning the role of regulation, the impact on investor confidence, and differences in short- and long-term stock performance. For both analyses, Refinitiv market data, Excel and advanced visualisations created in Microsoft Power BI were used. For better reading and grammatical correctness, this document was partially edited using AI tools like OpenAI's ChatGPT and Google's Gemini. The findings show that greenwashing can significantly reduce investor trust and short-term financial performance, while genuine and transparent sustainability practices can help restore market stability.
Vedoucí práce: Petr Teplý
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: bankovnictví a pojišťovnictví [obor bakal. práce]; bakalářské práce; bachelor's theses